STEM-based digital disaster learning model for disaster adaptation ability of elementary school students - Arwin, Arwin; Kenedi, Ary Kiswanto; Anita, Yesi; Hamimah, Hamimah; Handrianto, Ciptro; Zainil, Melva (Institute of Advanced Engineering and Science, 2024)
Efforts are required to enhance community resilience to disasters, especially among elementary school students who are highly vulnerable to losses caused by natural disasters. In previous research, a science, technology, engineering, and mathematics (STEM) based digital disaster learning model was developed for elementary school students, so further research is needed to determine its effect on the adaptability of elementary school students. This study aimed to assess the impact of the STEM-based digital disaster learning model on the disaster adaptation abilities of elementary school students. This research is a quasi-experimental. The data collection instrument is the disaster adaptation ability essay test questions. The data analysis process uses the help of the SPSS 26 application. The findings found an average difference in students' disaster adaptation abilities between STEM-based digital learning models and conventional learning models. This finding was also reinforced by the post-test average scores of students who studied using STEM-based digital disaster learning models, which were higher than those with conventional learning models. So overall, the STEM-based digital disaster learning model increases elementary school students' disaster adaptation abilities. The implications of this research can be used as a reference in developing elementary school students' disaster adaptation abilities.